THE EFFECT OF JOB SATISFACTION AND EMPLOYEE PERFORMANCE TO THE COMPANY'S MOTIVATION AND LEADERSHIP STYLE (STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE) - Sukmo Hadi Nugroho; Adi Bandono; Okol Sri Suharyo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
Previous research or relevant research is very important in research or scientific article where previous research or relevant research can serve to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews how the Determination of Job Satisfaction (Y1) and Employee Performance (Y2) on Motivation (X1) and Leadership Style (X2) in a Human Resource Management Literature Study. The results of this research library are that: 1) Motivation has a positive and significant effect on Job Satisfaction; 2) Leadership has a positive and significant effect on Job Satisfaction; 3) Motivation has a positive and significant effect on performance; 4) Leadership has a positive and significant effect on performance; and 5) Job Satisfaction has a positive and significant effect on performance. Keyword: Job Satisfaction, Employee Performance, Motivation, Leadership Style.